2016
DOI: 10.1016/j.applthermaleng.2016.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Generation of entropy and forced convection of heat in a conduit partially filled with porous media – Local thermal non-equilibrium and exothermicity effects

Abstract: h i g h l i g h t sLocal and total entropy generations in endothermic/exothermic channels are investigated. Convection interface boundary condition has been incorporated into the modelling. Partial filling of the channel with LTE and LTNE for energy equations are considered. Bifurcation phenomena for temperature and local entropy generation are observed. Analytical solutions for temperature and entropy generation rates are obtained. a b s t r a c tThe performance of a two-dimensional, axisymmetric channel with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…A general feature of these figures is the clear distinction between the temperature fields of the fluid and porous solid phases, rendering a strong deviation from local thermal equilibrium (LTE). This is consistent with the findings of the previous investigations of internally heat generating porous channels[25,48,60] and highlights the significance of LTNE approach in the current analysis. The effects of variation in the thermal conductivity ratio, , are shown inFig.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…A general feature of these figures is the clear distinction between the temperature fields of the fluid and porous solid phases, rendering a strong deviation from local thermal equilibrium (LTE). This is consistent with the findings of the previous investigations of internally heat generating porous channels[25,48,60] and highlights the significance of LTNE approach in the current analysis. The effects of variation in the thermal conductivity ratio, , are shown inFig.…”
supporting
confidence: 92%
“…The heat flux is then split based on the thermal conductivities of the respective phases of the porous material and the corresponding temperature gradients. Splitting the heat flux in this manner is referred to as Model A [25,[44][45][46] and has been widely used in literature (see for example [39,40,47,48]). In enacting this procedure, the effective thermal conductivity of each phase is used.…”
Section: Analytical Methods 21 Model Concept Configuration and Assumentioning
confidence: 99%
“…Although using LTNE method is more costly compared with LTE, it is more reliable and provides more accurate results prediction of the temperature fields inside the system [16]. Most importantly, it has been recently shown that the results of this approach are superior to those of LTE, particularly in the presence of heat generating/consuming chemical reactions [10] [17]. This superiority also improves the mass transfer analysis when the dispersion and energy equations of the fluid phase are coupled by the thermal diffusion of mass [18] [19].…”
Section: Introductionmentioning
confidence: 99%
“…A few points follow from the preceding review of literature. First, the general problem of partially filled porous channels and microchannels have already received significant attention, see for example [17] [25][26] [27]. As an essential commonality, all these investigations ignore the existence of the channel walls.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been applied by a number of scholars to investigate the effects of radiation on the entropy generation of thermal systems [41]. Hence, the local entropy generation rate across the entire microchannel can be formulated as follows [42][43][44]. …”
Section: Governing Equationsmentioning
confidence: 99%